Use of cork residues to control turfgrass diseases - Coelho, Luísa (2020)
The worldwide increase in agricultural and industrial production has created environmental problems. Economic and environmental benefits can be gathered solving a problem of the agroindustry by applying their sub products to soil. The compromise to decrease the use of pesticides and fertilizers, which may be hazardous, has provided opportunities for the development of new sustainable crop management practices. From several strategies to enhance the use of organic matter in agriculture, one has been the use of composts of different mixtures of raw materials, from different agroindustry processes or the use of these raw material (agroindustry residues) directly without any treatment. The incorporation of these products to the soil and its application to the crops proved to be an interesting pathway to apply effective beneficial microorganisms for the crops and for the ecosystems globally. This strategy showed to achieve reasonable crops yields and suppressive effects on phytopathogenic microorganisms. Several microorganisms have been associated to cork throughout tree life and in the end products1, such as Trichoderma pseudoconingii, T. viride, Endothiella gyrosa, Mucor hiemalis, Rhysopus sp., Penicillium sp., Cytospora sp., Dichomera sp., Acremonium sp., Glyocladium sp., Botrytis silvatica, and Pestalotia sp. Considering the potential of these microorganisms, a study was carried out at the University of Algarve to identify the presence of beneficial microorganisms in cork residues and to evaluate, in vitro, their antagonistic effect against several fungi turfgrass diseases.